Diaphragm and preparation method thereof, battery and electric device
By using separators prepared with functional group functional polymers in lithium-ion batteries, the transition metal ion interception problem is solved, significantly improving battery performance and safety.
Patent Information
- Application Number
- CN202411908173.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively intercept and remove transition metal ions, such as iron, nickel, copper, zinc, etc. in lithium-ion batteries, resulting in reduced battery performance and safety hazards.
Functional polymers with functional groups are used as the separator material to effectively intercept and bind transition metal ions through complexing and/or charge attraction to prevent them from diffusing to the negative electrode side.
Effectively protect battery performance, prevent self-discharge and capacity attenuation caused by transition metal ions, reduce safety risks, and achieve effective control of metal foreign matter in lithium-ion batteries.
Smart Images

Figure CN119833876A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art
[0002] For lithium-ion batteries, metal foreign matter impurities have a great impact on battery performance. Metal foreign matter can cause large self-discharge and capacity decay of lithium-ion batteries. In severe cases, it may pierce the diaphragm and cause battery short circuit, leading to safety problems. Therefore, metal foreign matter in lithium-ion batteries needs to be strictly controlled.
[0003] At present, in the production of lithium-ion batteries, magnetic particles in battery slurry are mainly intercepted through demagnetization devices to reduce metal foreign matter such as iron and nickel in positive and negative electrode slurries. However, this measure also has obvious shortcomings: the interception ability of magnetic metal particles is limited, stainless steel particles cannot be intercepted, and non-magnetic foreign matter such as copper, zinc, and aluminum cannot be intercepted. For assembled lithium-ion batteries, there is currently no effective means to remove or passivate metal ions.
[0004] Therefore, the current technology related to the control of metal foreign matter in lithium-ion batteries still needs to be improved. Summary of the invention
[0005] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a diaphragm capable of effectively anchoring transition metal ions.
[0006] In the first aspect of the present application, a diaphragm is provided. According to an embodiment of the present application, the diaphragm includes: a functional polymer, wherein the functional polymer has a functional group, wherein the functional group can anchor transition metal ions, and the anchoring is achieved by complexation and / or charge attraction. During the charging and discharging process of a battery using the diaphragm, transition metal ions such as iron, nickel, copper, and zinc migrate with the electrolyte. During the process of penetrating the diaphragm, the transition metal ions can undergo complexation and / or charge attraction with the functional groups in the functional polymer, so that the transition metal ions are intercepted and bound by the functional polymer layer in the diaphragm and cannot diffuse to the negative electrode side, thereby protecting the battery performance.
[0007] According to an embodiment of the present application, the diaphragm includes a first base film and a polymer layer, wherein the polymer layer is located on at least one surface of the first base film in a thickness direction.
[0008] According to an embodiment of the present application, the diaphragm further includes a second base film, and the polymer layer is located between the first base film and the second base film.
[0009] According to an embodiment of the present application, the first base film has pores, and at least a portion of the polymer layer is located in the pores.
[0010] According to an embodiment of the present application, the diaphragm includes a diaphragm body and a functional polymer dispersed in the diaphragm body.
[0011] According to an embodiment of the present application, the number average molecular weight of the functional polymer is 5W to 80W, and specifically can be 15W to 60W.
[0012] According to an embodiment of the present application, the functional group includes at least one of a first functional group and a second functional group; the first functional group has an atom containing a lone pair of electrons; and the second functional group includes an electronegative group and / or atom.
[0013] According to an embodiment of the present application, in the functional polymer, the quantity ratio of the first functional group to the second functional group is 1:1-3.
[0014] According to an embodiment of the present application, the first functional group includes at least one of nitrogen, phosphorus and sulfur. Specifically, the first functional group includes at least one of amino, C=NNHR, amide, cyano, phosphoramide, and phosphorimide, wherein R includes at least one of alkyl, alkoxy, and phenyl.
[0015] According to an embodiment of the present application, the second functional group includes at least one of a halogen, a carbonyl, a hydroxyl, and an ester group. Specifically, the second functional group includes at least one of a carboxyl group and an ester group.
[0016] According to an embodiment of the present application, the functional polymer includes a main chain and a side chain, the main chain is a carbon chain, and the side chain includes the functional group.
[0017] According to an embodiment of the present application, the monomer of the functional polymer includes at least one of 2-acetamido-2-vinylacetic acid, 2,2'-((4-vinylbenzyl)amino)diacetic acid, a compound containing -N-CH2COOH, and a compound containing -N-CH2CH2COOH.
[0018] According to an embodiment of the present application, the functional polymer includes at least one of the following compounds:
[0019]
[0020] Here, n is the degree of polymerization.
[0021] In a second aspect of the present application, a method for preparing the aforementioned diaphragm is provided. According to an embodiment of the present application, the method comprises: forming a polymer layer on at least one surface of a first base film to obtain the diaphragm.
[0022] According to an embodiment of the present application, the method further includes: forming a second base film on a surface of the polymer layer away from the first base film to obtain the diaphragm.
[0023] According to an embodiment of the present application, the polymer layer is formed by coating, coextrusion, or dipping.
[0024] In a third aspect, the present application provides a method for preparing the aforementioned diaphragm. According to an embodiment of the present application, the method comprises: mixing and melting a diaphragm body raw material and a functional polymer to obtain a molten mixture, and extruding the molten mixture to obtain the diaphragm.
[0025] In a fourth aspect of the present application, a battery is provided. According to an embodiment of the present application, the battery includes the aforementioned diaphragm. During the charge and discharge process of the battery, transition metal ions such as iron, nickel, copper, and zinc migrate with the electrolyte. In the process of penetrating the diaphragm, the transition metal ions can undergo complexation and / or charge attraction with the functional groups in the functional polymer, so that the transition metal ions are intercepted and bound by the functional polymer layer in the diaphragm and cannot diffuse to the negative electrode side, thereby protecting the battery performance.
[0026] In a fifth aspect, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described above. The electric device has all the features and advantages of the battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application.
[0028] Figure 2 It is a schematic structural diagram of a diaphragm according to another embodiment of the present application.
[0029] Figure 3 It is a schematic structural diagram of a diaphragm according to another embodiment of the present application.
[0030] Figure 4 A schematic structural diagram of a diaphragm according to another embodiment of the present application.
[0031] Figure 5 It is a graph showing the high temperature cycle performance test results of the lithium ion batteries in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0033] In the first aspect of the present application, a diaphragm is provided. According to an embodiment of the present application, the diaphragm includes: a functional polymer, wherein the functional polymer has a functional group, wherein the functional group can anchor transition metal ions, and the anchoring is achieved by complexation and / or charge attraction. During the charging and discharging process of a battery using the diaphragm, transition metal ions such as iron, nickel, copper, and zinc migrate with the electrolyte. During the process of penetrating the diaphragm, the transition metal ions can undergo complexation and / or charge attraction with the functional groups in the functional polymer, so that the transition metal ions are captured and bound by the functional polymer layer in the diaphragm, and cannot diffuse to the negative electrode side for deposition, thereby playing a "self-cleaning" role, thereby protecting the battery performance.
[0034] It is understood that the form in which the functional polymer exists in the separator is not particularly limited, as long as it can be complexed with and / or charge-attracted by the transition metal ions.
[0035] In the present application, there is no particular limitation on the specific types of transition metal ions that can be intercepted by the diaphragm, including but not limited to iron, nickel, copper, zinc, chromium, manganese, tin, molybdenum, titanium, etc.
[0036] In some embodiments, reference Figure 1 and Figure 2 The diaphragm includes a first base film 11 and a polymer layer 13 located on at least one surface of the first base film 11 in a thickness direction, wherein the polymer layer 13 includes the functional polymer.
[0037] In some embodiments, reference Figure 3 The separator includes a first base film 11, a second base film 12 and a polymer layer 13, wherein the polymer layer 13 is located between the first base film 11 and the second base film 12, and the polymer layer 13 includes the functional polymer. The three-layer composite separator has base films on both sides, which can play an insulating support role, and the middle layer is a polymer layer containing functional polymers, which is used to intercept transition metal foreign ions in the battery.
[0038] In some embodiments, the first base film has pores, and at least a portion of the polymer layer is located in the pores.
[0039] In some embodiments, reference Figure 4 The diaphragm includes a diaphragm body 41 and a functional polymer 42 dispersed in the diaphragm body 41 .
[0040] Herein, the functional polymer dispersed in the separator body refers to the situation where the functional polymer is mixed with the raw materials forming the separator body and then made into the separator.
[0041] Specifically, the above different settings can effectively intercept transition metal ions. When actually used in batteries, the environment near the positive electrode is strongly oxidizing, and the environment near the negative electrode is strongly reducing. Functional polymers are easily affected in strong oxidizing or reducing environments, which is not conducive to their performance. Therefore, the functional polymer can be set between the two layers of base film, so that the functional polymer can be in an inert environment, reducing the impact of the positive and negative electrodes on the functional polymer.
[0042] It can be understood that the first base film, the second base film, and the diaphragm body can be conventional diaphragms, for example, the material of the conventional diaphragm can include but is not limited to one or more of high-density polyethylene, ultra-high-density polyethylene, low-density polyethylene, linear low-density polyethylene, high-density polypropylene, ultra-high-density polypropylene, polyimide, and polyvinylidene fluoride. And the base film and the diaphragm body can be a single-layer structure or a multi-layer composite structure, which is not particularly limited in this application.
[0043] According to an embodiment of the present application, the number average molecular weight of the functional polymer is 5W to 80W, specifically 15W to 60W. As an example, the number average molecular weight of the functional polymer can be 5W, 6W, 7W, 8W, 9W, 10W, 11W, 12W, 13W, 14W, 15W, 16W, 17W, 18W, 19W, 20W, 25W, 30W, 35W, 40W, 45W, 50W, 55W, 60W, 65W, 70W, 75W, 80W, etc. It can be understood that when the diaphragm is used in a battery, the functional polymer is usually immersed in an electrolyte. At this time, the functional polymer may absorb the electrolyte to swell, thereby causing the functional polymer to diffuse. The use of a functional polymer with a larger molecular weight can effectively improve the problem of swelling and diffusion of the functional polymer. If the molecular weight is too low, it may not be easy to form a film and stretch, and it may break easily; if the molecular weight is too high, it may lead to high melt viscosity and increased processing difficulty.
[0044] According to an embodiment of the present application, in order to obtain better complexation and / or charge attraction with transition metal ions, the functional group includes at least one of a first functional group and a second functional group, wherein the first functional group has an atom containing a lone pair of electrons; and the second functional group includes an electronegative group and / or atom. Thus, the functional group has a negative charge or a lone pair of electrons, and can effectively combine with transition metal ions to achieve the effect of intercepting transition metal ions.
[0045] In some specific embodiments, the functional polymer has a first functional group. In other embodiments, the functional polymer has a first functional group and a second functional group. Specifically, the first functional group can complex with transition metal ions, thereby intercepting the migration of metal ions to the negative electrode for deposition, while the second functional group carries a negative charge and can combine with positively charged transition metal ions through charge attraction. The two can synergistically form a 5-membered ring or 6-membered ring structure with better stability, thereby stably intercepting transition metal ions.
[0046] According to an embodiment of the present application, the atom with a lone pair of electrons in the first functional group includes at least one of nitrogen, phosphorus and sulfur, that is, the first functional group includes at least one of nitrogen, phosphorus and sulfur. In some specific embodiments, the first functional group includes at least one of amino, C=NNHR, amide, cyano, phosphoramidite, and phosphoramidite, wherein R includes at least one of alkyl, alkoxy, and phenyl. Thus, the atom containing a lone pair of electrons can effectively complex with transition metal ions, thereby blocking transition metal ions.
[0047] According to an embodiment of the present application, the second functional group includes at least one of a halogen, a carbonyl, a hydroxyl, and an ester group. In some specific embodiments, the second functional group includes at least one of a carboxyl group and an ester group. Thus, the second functional group carrying a negative charge can anchor the transition metal ion by charge attraction, and can also synergize with the first functional group to further enhance the effect of anchoring the transition metal ion.
[0048] According to an embodiment of the present application, in the functional polymer, the number ratio of the first functional group to the second functional group is 1:1 to 3, specifically, 1:1, 1:2, 1:3, etc. Thus, the electronegativity of the second functional group attracts transition metal ions, and the atoms with lone pairs of electrons in the first functional group form coordination bonds with transition metal ions. The above-mentioned ratio of the two is more conducive to forming a 5-membered ring or 6-membered ring structure with better stability, which is conducive to stabilizing the binding of transition metal ions, and the more charge-attracting structures surrounding the transition metal ions, the better the stability.
[0049] As an example, the above 5-membered ring structure may include but is not limited to the following similar structures;
[0050]
[0051] According to an embodiment of the present application, the functional polymer includes a main chain and a side chain, wherein the main chain is a carbon chain, and the side chain includes the functional group. As an example, the main chain of the functional polymer can be a carbon chain formed by free radical polymerization of olefin groups. With the above structure, the functional polymer has a wider range of choices and is easy to prepare.
[0052] According to an embodiment of the present application, the monomer includes at least one of 2-acetamido-2-vinylacetic acid, 2,2'-((4-vinylbenzyl)aminoylidene)diacetic acid, a compound containing -N-CH2COOH, and a compound containing -N-CH2CH2COOH.
[0053] According to an embodiment of the present application, the functional polymer includes at least one of the following compounds:
[0054]
[0055] Wherein, n and n1 are the degree of polymerization, which can be flexibly selected according to the molecular weight of the functional polymer and are not particularly limited in the present application.
[0056] It is understood that the functional polymer can be formed from monomer molecules through aqueous free radical polymerization to form a macromolecular polymer; the specific operation can be flexibly selected according to actual needs. As an example, the reaction temperature of the monomer molecules through aqueous free radical polymerization can be 40°C to 90°C, such as 60°C to 75°C, etc.; the initiator addition time in the initiation stage can be 0 hours to 4 hours, such as 2 hours to 3 hours; the heat preservation reaction time in the chain growth stage can be 0 hours to 6 hours, such as 3 hours to 4 hours, etc.
[0057] According to an embodiment of the present application, the pore size of the above-mentioned diaphragm can be 20nm to 70nm, specifically 20nm, 30nm, 40nm, 50nm, 60nm, and 70nm. This pore size range is conducive to the passage of active ions and has a good effect of anchoring transition metal ions.
[0058] According to an embodiment of the present application, the porosity of the separator may be 20% to 70%, specifically 20%, 30%, 40%, 50%, 60%, 70%, etc. The porosity is conducive to the passage of active ions, and has good insulation properties, which can effectively isolate the positive electrode sheet and the negative electrode sheet.
[0059] According to the embodiments of the present application, the air permeability of the diaphragm can be 50s / 100cc to 500s / 100cc, such as 50s / 100cc, 100s / 100cc, 150s / 100cc, 200s / 100cc, 250s / 100cc, 300s / 100cc, 350s / 100cc, 400s / 100cc, 450s / 100cc, 500s / 100cc, etc. Thus, the performance of the diaphragm can be brought into play.
[0060] According to the embodiments of the present application, the thickness of the separator can be 2 μm to 40 μm, specifically 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc. This thickness range can be applied to most batteries and has a wider range of applications.
[0061] In a second aspect of the present application, a method for preparing the aforementioned diaphragm is provided. According to an embodiment of the present application, the method comprises: forming a polymer layer on at least one surface of a first base film to obtain the diaphragm.
[0062] According to an embodiment of the present application, the polymer layer may be formed by coating, coextrusion or dipping.
[0063] In some embodiments, the coating to form the polymer layer may be performed by dispersing the functional polymer in a solvent to obtain a functional polymer dispersion, and then coating the functional polymer dispersion on at least one surface of the first base film, and drying to form a polymer layer on at least one side of the first base film. Figure 1 or Figure 2 Diaphragm shown.
[0064] It is understood that the solvents that can be used to prepare the functional polymer dispersion include but are not limited to water, acetone, N-methylpyrrolidone, etc. The specific coating steps and coating parameters can be flexibly adjusted and selected according to the actual situation, as long as the polymer layer can be effectively formed, and this application does not impose any special restrictions.
[0065] In other embodiments, the polymer layer can be formed by coextrusion by coextruding the raw material of the first base film and the functional polymer to obtain a diaphragm having a polymer layer on one side of the first base film or having a polymer layer on both sides of the first base film. The specific coextrusion process steps, parameters, etc. can be selected according to actual needs and are not particularly limited in this application.
[0066] In some other embodiments, the polymer layer can be formed by immersing the first base film in a dispersion containing a functional polymer, and the first base film can be taken out and dried to obtain the diaphragm. In this step, the functional polymer can be dispersed in a solvent to form a functional polymer dispersion, and the base film can be immersed in the functional polymer dispersion to allow the functional polymer molecules to freely diffuse into the pores of the first base film, and then the first base film can be dried to obtain a diaphragm in which the functional polymer is attached to the surface of the first base film and a portion of the functional polymer is filled in the pores of the first base film.
[0067] According to an embodiment of the present application, the method further includes: disposing a second base film on a surface of the polymer layer away from the first base film to obtain the diaphragm.
[0068] In some embodiments, after the functional polymer dispersion is coated on one surface of the first base film and dried, the second base film is placed on the surface of the polymer layer away from the first base film, and then heat-treated to soften the second base film and connect it to the polymer layer to form a tightly fitted three-layer composite diaphragm (see the structural schematic diagram). Figure 3 ), the polymer layer is located between the first base film and the second base film. The heat treatment can be performed at a temperature 5°C to 30°C lower than the melting point of the second base film for 1 min to 120 min.
[0069] In other embodiments, the first base film raw material, the second base film raw material and the functional polymer can be co-extruded to directly obtain a three-layer structured separator in which the polymer layer is located between the first base film and the second base film. It is understood that the co-extruded film layer can also be post-processed by stretching, extraction and other processes.
[0070] It is understood that the specific operation steps and parameters of the co-extrusion can be flexibly adjusted according to actual needs, and this application does not impose any particular restrictions. For example, it can be carried out with reference to conventional techniques.
[0071] In a third aspect, the present application provides a method for preparing the aforementioned diaphragm. According to an embodiment of the present application, the method comprises: mixing and melting the diaphragm body raw material and the functional polymer to obtain a molten mixture, extruding the molten mixture to obtain the diaphragm (see the schematic diagram of the structure) Figure 4 ).
[0072] In some embodiments, the raw material of the diaphragm body and the functional polymer can be mixed and melted to form a uniform fluid, and then extruded into a cast sheet, which can then be subjected to processes such as stretching and extraction to obtain a diaphragm in which the raw material of the diaphragm body (such as polyolefin molecules) and the functional polymer molecules are entangled with each other, that is, a diaphragm in which the functional polymer is dispersed in the diaphragm body.
[0073] It can be understood that the specific operation steps and parameters of the extrusion in this method are not particularly limited and can be flexibly adjusted according to the requirements of the target membrane.
[0074] It should be noted that in the above-mentioned method for preparing the diaphragm, the first base film and / or the second base film are formed simultaneously in the extrusion treatment and co-extrusion treatment steps, and the first base film and / or the second base film used in the coating and soaking steps are the already prepared first base film and / or the second base film, which can be prepared by conventional technical methods in the field, such as wet film making, dry film making, etc., and the present application does not impose any special restrictions.
[0075] In a fourth aspect of the present application, a battery is provided. According to an embodiment of the present application, the battery includes the aforementioned diaphragm. During the charge and discharge process of the battery, transition metal ions such as iron, nickel, copper, and zinc migrate with the electrolyte. In the process of penetrating the diaphragm, the transition metal ions can undergo complexation and / or charge attraction with the functional groups in the functional polymer, so that the transition metal ions are intercepted and bound by the functional polymer layer in the diaphragm and cannot diffuse to the negative electrode side, thereby protecting the battery performance.
[0076] It can be understood that there is no other limitation on the specific type of the battery, including but not limited to lithium-ion batteries, sodium-ion batteries, etc., and the battery can be a square shell battery, a soft pack battery, a cylindrical battery, etc., and can be in different forms such as a battery cell, a battery module, a battery pack, etc.
[0077] It can also be understood that in addition to the aforementioned separator, the battery may also include other necessary structures and components of conventional batteries. Taking a lithium-ion battery as an example, it may include an outer package, and an electrode assembly and an electrolyte contained in the outer package, and the electrode assembly may include a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet.
[0078] As an example, the positive electrode sheet may include a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, and the positive electrode film layer generally contains a positive electrode active material, a conductive agent, and a binder. The negative electrode sheet may include a negative electrode current collector and a negative electrode film layer located on at least one side of the negative electrode current collector, and the negative electrode film layer generally contains a negative electrode active material, a conductive agent, and a binder. The electrolyte generally may include an electrolyte salt and a solvent. The above-mentioned positive electrode active material, binder, conductive agent, current collector, electrolyte salt, and solvent can be selected with reference to conventional technology, and this application does not impose any special restrictions.
[0079] In some embodiments, the positive electrode active material includes but is not limited to lithium transition metal oxides and / or lithium phosphates with olivine structure. Specifically, the lithium transition metal oxides include lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as NCM333, NCM523, NCM211, NCM622, NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) or a combination thereof; olivine-structured lithium-containing phosphates include but are not limited to lithium iron phosphate (such as LiFePO4), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate (such as LiMn x Fe 1-xPO4, 0<x<1), at least one of a composite material of lithium manganese iron phosphate and carbon.
[0080] In some embodiments, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, which is not limited in the embodiments of the present application.
[0081] In some embodiments, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) and carboxymethyl chitosan (CMCS).
[0082] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0083] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0084] In some embodiments, the negative electrode active material may include one or more of a carbon-based material, a silicon-based material, a tin-based material, and lithium titanate. The carbon-based material may include one or more of graphite (e.g., artificial graphite, natural graphite, etc.), soft carbon, and hard carbon. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys.
[0085] In some embodiments, the negative electrode film layer may include a negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS), and the embodiments of the present application are not limited thereto.
[0086] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, which is not limited in the present embodiment.
[0087] In some embodiments, the electrolyte salt may include at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluoroborate.
[0088] In some embodiments, the organic solvent in the electrolyte may include one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl formate, ethyl acetate, methyl acetate, fluoroethylene carbonate, difluoroethylene carbonate, fluoroethyl methyl carbonate, fluorodiethyl carbonate, ethyl fluoroformate, fluoroethyl acetate, and fluoromethyl acetate.
[0089] In a fifth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the battery described above. The electric device has all the features and advantages of the battery described above, which will not be described one by one here.
[0090] According to an embodiment of the present application, the power-consuming device may include a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto. The battery may be used as a power source for the power-consuming device, or may be used as an energy storage unit for the power-consuming device.
[0091] It can be understood that in addition to the battery mentioned above, the electrical device can also include the necessary structures and components of conventional electrical devices. Taking electric vehicles as an example, they can include the necessary structures and components such as the body, windows, chassis, engine, seats, tires, etc., which will not be repeated here.
[0092] The embodiments of the present application are described in detail below.
[0093] Example 1
[0094] Preparation of functional polymer: Add monomer (2-acetylamino-2-vinyl acetic acid) solution into the reaction device, introduce nitrogen to drive out oxygen for 15 minutes, and heat to 65°C; take 1.0% of the monomer mass of potassium persulfate (K2S2O8) and dissolve it in water, slowly add potassium persulfate aqueous solution to the monomer solution, and add it over 2 hours; continue to keep warm and react for 4-6 hours; cool down, filter the finished material, and dry the filtrate to obtain a functional polymer solid with a number average molecular weight of 45w and a quantitative ratio of the first functional group (acetylamino) to the second functional group (carboxyl) of 1:1.
[0095] Preparation of diaphragm: ① Melt the PE raw material and functional polymer separately, and extrude the diaphragm extrusion casting segment in three layers, the upper and lower layers are PE melt, and the middle layer is poly (2-acetylamino-2-vinyl acetate) melt; ② The extruded film is stretched, extracted, heat-set, etc., and rolled up to obtain a three-layer diaphragm (see the structural diagram) Figure 3 );
[0096] Preparation of lithium-ion battery: Take lithium iron phosphate positive electrode sheet, graphite negative electrode sheet and separator, first use inductively coupled plasma optical emission spectrometer (ICP-OES) to detect the metal ion content, and then assemble it into a lithium-ion battery with electrolyte (lithium salt is 1.0 mol / L LiPF6, and the solvent is ethylene ester (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1). The battery is charged and discharged 500 times, and the metal element content of the positive electrode sheet, negative electrode sheet and separator is detected respectively. The test results are shown in Table 1.
[0097] Example 2
[0098] Preparation of functional polymer: Add the monomer (2-acetylamino-2-vinyl acetic acid) solution to the reaction device, introduce nitrogen to drive out oxygen for 15 minutes, and heat to 65°C; take 1.0% of the monomer mass of potassium persulfate (K2S2O8) and dissolve it in water, slowly add the potassium persulfate aqueous solution to the monomer solution, and add it over 2 hours; continue to keep warm and react for 4-6 hours; cool down, filter the finished material, dry the filtrate, and obtain a functional polymer solid with a number average molecular weight of 45w and a ratio of the first functional group (acetylamino) to the second functional group (carboxyl) of 1:1. The number average molecular weight is detected by gel permeation chromatography (GPC for short), and the ratio of the first functional group (acetylamino) to the second functional group (carboxyl) is detected by nuclear magnetic resonance hydrogen spectrum.
[0099] Preparation of diaphragm: ① Add appropriate amount of deionized water to the aqueous dispersion of functional polymer to adjust the solid content to 30%; ② Take PE diaphragm, apply the functional polymer dispersion on the surface of PE diaphragm, and dry; ③ Take another layer of PE diaphragm, place it on the other side of the functional polymer layer, and perform heat treatment to form a tightly fitted three-layer composite diaphragm;
[0100] Preparation of lithium ion battery: same as in Example 1.
[0101] Example 3
[0102] Preparation of diaphragm: ① Disperse the functional polymer (same as Example 1) in water, add dispersant, binder, etc. to make a coating slurry; ② Take a PE diaphragm and coat the prepared slurry on the surface of the diaphragm; ③ Dry the diaphragm and roll it up to obtain a PE diaphragm with a functional coating.
[0103] Preparation of lithium ion battery: same as in Example 1.
[0104] Example 4
[0105] Preparation of diaphragm: ① Completely dissolve the functional polymer (same as Example 1) in acetone to form a dilute solution; ② Take a PE diaphragm and immerse the base film in the functional polymer solution to allow the functional polymer molecules to penetrate into the pores of the diaphragm; ③ Dry the diaphragm to obtain a PE diaphragm filled with functional polymer molecules.
[0106] Preparation of lithium ion battery: same as in Example 1.
[0107] Example 5
[0108] Preparation of diaphragm: ① Mix the functional polymer solid (same as in Example 1) with the PE powder and heat them together to form a uniformly mixed melt; ② After co-extrusion, casting, stretching, extraction and other processes, a uniform diaphragm containing the functional polymer is obtained.
[0109] Preparation of lithium ion battery: same as in Example 1.
[0110] Comparative Example 1
[0111] Same as Example 1, except that the diaphragm is a common PE diaphragm.
[0112] Performance Test:
[0113] The prepared lithium-ion battery was placed in a 60°C environment and subjected to a charge and discharge test at a 1C rate with a charge and discharge voltage range of 2.0V to 3.8V. The cycle performance curves of the lithium-ion batteries in Example 1 and Comparative Example 1 are shown in FIG. Figure 5 .
[0114] Table 1
[0115]
[0116] Note: ND: not detected.
[0117] It can be seen from the above test results that by adopting the diaphragm of the present application, transition metal ions can be effectively intercepted, the problem of transition metal deposition at the negative electrode can be improved, and the electrochemical performance of the battery can be improved.
[0118] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0119] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0120] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A diaphragm, characterized in that: The invention comprises a functional polymer, wherein the polymer has a functional group, and the functional group can anchor transition metal ions, and the anchoring is achieved by complexation and / or charge attraction.
2. The diaphragm according to claim 1, characterized in that The invention comprises a first base film and a polymer layer, wherein the polymer layer is located on at least one side surface of the first base film in a thickness direction.
3. The diaphragm according to claim 2, characterized in that A second base film is also included, and the polymer layer is located between the first base film and the second base film.
4. The diaphragm according to claim 2, characterized in that The first base film has pores, and at least a portion of the polymer layer is located in the pores.
5. The diaphragm according to claim 1, characterized in that The invention comprises a diaphragm body and a functional polymer dispersed in the diaphragm body.
6. The diaphragm according to claim 1, characterized in that The number average molecular weight of the functional polymer is 5W to 80W, preferably 15W to 60W.
7. The diaphragm according to any one of claims 1 to 6, characterized in that The functional group includes at least one of a first functional group and a second functional group; The first functional group has an atom having a lone pair of electrons; The second functional group includes a group and / or an atom having electronegativity.
8. The diaphragm according to claim 7, characterized in that In the functional polymer, the quantity ratio of the first functional group to the second functional group is 1:1-3.
9. The diaphragm according to claim 7, characterized in that The first functional group includes at least one of nitrogen, phosphorus and sulfur, preferably the first functional group includes at least one of amino, C=NNHR, amide, cyano, phosphoramide, phosphoramidite, wherein R includes at least one of alkyl, alkoxy and phenyl.
10. The diaphragm according to claim 7, characterized in that The second functional group includes at least one of halogen, carbonyl, hydroxyl and ester, and preferably includes at least one of carboxyl and ester.
11. The diaphragm according to claim 1, characterized in that The functional polymer comprises a main chain and a side chain, wherein the main chain is a carbon chain and the side chain comprises the functional group.
12. The diaphragm according to claim 11, characterized in that The monomer of the functional polymer includes at least one of 2-acetamido-2-vinyl acetic acid, 2,2'-((4-vinylbenzyl)aminoylidene)diacetic acid, a compound containing -N-CH2COOH, and a compound containing -N-CH2CH2COOH.
13. The diaphragm according to claim 12, characterized in that The functional polymer comprises at least one of the following compounds: Where n and n1 are the degrees of polymerization.
14. A method for preparing the diaphragm according to any one of claims 1 to 4 and 6 to 13, characterized in that: include: A polymer layer is formed on at least one surface of a first base film to obtain the separator.
15. The method according to claim 14, characterized in that Also includes: A second base film is disposed on a surface of the polymer layer away from the first base film to obtain the separator.
16. The method according to claim 14 or 15, wherein the polymer layer is formed by coating, coextrusion, or dipping.
17. A method for preparing the diaphragm according to any one of claims 1, 5 to 13, characterized in that: include: The separator body raw material and the functional polymer are mixed and melted to obtain a molten mixture, and the molten mixture is extruded to obtain the separator.
18. A battery, characterized in that: A separator comprising the separator according to any one of claims 1 to 13.
19. An electrical device, characterized in that: Comprising the battery of claim 18.
Citation Information
Patent Citations
Gel polymer modified lithium ion battery diagraph and preparing method and application thereof
CN104377330A
Lithium battery membrane and preparation method thereof and lithium battery using membrane
CN106898719A
Lithium ion battery
CN107528086A
Metal ion transport material and preparation method and application thereof
CN115787122A
Polymer particles
CN117897412A
Cited By
Sodium-ion battery diaphragm, preparation method thereof and sodium-ion battery
CN120376884A
Battery and electric device
CN121416515A